2014
DOI: 10.1038/nature12917
|View full text |Cite
|
Sign up to set email alerts
|

A millisecond pulsar in a stellar triple system

Abstract: Gravitationally bound three-body systems have been studied for hundreds of years 1, 2 and are common in our Galaxy 3, 4 . They show complex orbital interactions, which can constrain the compositions, masses, and interior structures of the bodies 5 and test theories of gravity 6 , if sufficiently precise measurements are available. A triple system containing a radio pulsar could provide such measurements, but the only previously known such system, B1620−26 7, 8 (with a millisecond pulsar, a white dwarf, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
279
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(289 citation statements)
references
References 46 publications
8
279
1
1
Order By: Relevance
“…However, their eccentricities and orbital periods have led to the suggestion of an alternative hypothesis of direct MSP formation via a rotationally delayed accretion-induced collapse of a massive WD (Freire & Tauris 2014). Whereas the origin of these systems remains unclear, a triple system MSP with two WD companions (PSR J0337+1715) was announced earlier this year by Ransom et al (2014). This amazing system must have survived at least 3 phases of mass transfer and one SN explosion and challenges current knowledge of multiple stellar system evolution (Tauris & van den Heuvel 2014).…”
Section: Pulsar Recycling and Formation Of Exotic Binaries And Triplesmentioning
confidence: 99%
“…However, their eccentricities and orbital periods have led to the suggestion of an alternative hypothesis of direct MSP formation via a rotationally delayed accretion-induced collapse of a massive WD (Freire & Tauris 2014). Whereas the origin of these systems remains unclear, a triple system MSP with two WD companions (PSR J0337+1715) was announced earlier this year by Ransom et al (2014). This amazing system must have survived at least 3 phases of mass transfer and one SN explosion and challenges current knowledge of multiple stellar system evolution (Tauris & van den Heuvel 2014).…”
Section: Pulsar Recycling and Formation Of Exotic Binaries And Triplesmentioning
confidence: 99%
“…Article published by EDP Sciences A86, page 1 of 11 (Ransom et al 2014). Five planets, distributed within three planetary systems, are known to orbit pulsars (Wolszczan & Frail 1992;Thorsett et al 1993;Bailes et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the lowmass white dwarf is in a close binary with an unseen massive companion such as a neutron star, while the hotter, massive white dwarf is a wide companion. Recently, Ransom et al (2014) discovered a triple system in the Galactic disk consisting of a neutron star and two white dwarfs, of which one is very low mass, and hence nature is apparently producing such triple compact star systems (Tauris & van den Heuvel 2014). However, in this scenario the problem with the incompatible cooling ages and masses remains, unless the hot white dwarf was captured as the third component later on and did not form at the same time as the close binary.…”
Section: Discussionmentioning
confidence: 96%
“…New dedicated searches such as the ELM Survey have significantly increased the known population in recent years (Brown et al 2010Kilic et al 2011Kilic et al , 2012. The majority of ELM white dwarfs are companions to other white dwarfs (Kaplan et al 2014, this paper) or millisecond pulsars (see for example van Kerkwijk et al 1996;Bassa et al 2006;Antoniadis et al 2013) and a few have been found in hierarchical triple systems (Ransom et al 2014;Kilic et al 2014aKilic et al , 2015 or orbiting A-or F-type mainsequence stars (Maxted et al 2014;Breton et al 2012). The subject of this paper, SDSS J1257+5428, is a binary that likely belongs to the first of these classes, but, as we shall see, how it evolved into the system we see today is a mystery.…”
Section: Introductionmentioning
confidence: 99%